2008
DOI: 10.1001/archoto.2007.36
|View full text |Cite
|
Sign up to set email alerts
|

An Orthotopic Model of Papillary Thyroid Carcinoma in Athymic Nude Mice

Abstract: An orthotopic model of papillary thyroid carcinoma was successfully established in nude mice using BRAF-mutated and RET/PTC1-rearranged cell lines. These models mimic the human disease and will thus be useful for evaluating the clinical potential of novel targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 26 publications
2
47
0
1
Order By: Relevance
“…The human PTC cell line, BHP10-3 cells (passage number ranged from 9 to 12) -a tumorigenic clone of the BHP10-3 cell line containing the RET/PTC rearrangement, was developed and kindly provided by Dr Soon-Hyun Ahn (Seoul National University College of Medicine, Seoul, Korea) and Dr Gary L Clayman (MD Anderson Cancer Center, Houston, TX, USA) (Ahn et al 2008). The BRAF V600E -containing human PTC cell line, KTC1 cells (passage number ranged from 6 to 9), was a kind gift from Dr J K Chung (Seoul National University College of Medicine, Seoul, Korea).…”
Section: Cell Cultures and Harvesting Of Cell CMmentioning
confidence: 99%
“…The human PTC cell line, BHP10-3 cells (passage number ranged from 9 to 12) -a tumorigenic clone of the BHP10-3 cell line containing the RET/PTC rearrangement, was developed and kindly provided by Dr Soon-Hyun Ahn (Seoul National University College of Medicine, Seoul, Korea) and Dr Gary L Clayman (MD Anderson Cancer Center, Houston, TX, USA) (Ahn et al 2008). The BRAF V600E -containing human PTC cell line, KTC1 cells (passage number ranged from 6 to 9), was a kind gift from Dr J K Chung (Seoul National University College of Medicine, Seoul, Korea).…”
Section: Cell Cultures and Harvesting Of Cell CMmentioning
confidence: 99%
“…PTC is the most common thyroid malignancy and has excellent long-term survival with standard therapy (1). However, poorly differentiated and undifferentiated thyroid cancers more readily metastasize, frequently resist uptake of radioiodine treatments, and therefore lead to the largest number of endocrine-related deaths (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of orthotopic mouse models of ATC or PTC have been published previously (1,(19)(20)(21)(22)(23)(24)(25)(26). However, some of the tumor cell lines used in these studies were subsequently determined to be of melanoma and=or colon cancer due to contamination, rather than HTC cells lines as originally reported (27).…”
Section: Introductionmentioning
confidence: 99%
“…As several published studies of orthotopic models of thyroid cancer used cell lines that are now found to be derived from colon cancer or melanoma (14), one must be careful in the conclusions previously drawn about thyroid cancer biology. Orthotopic models of thyroid cancer have been shown to develop lymph node and pulmonary metastases, but not other sites of distant metastasis (20). To model bone metastasis, intracardiac or direct injection of tumor cells into bone is required (21).…”
Section: Introductionmentioning
confidence: 99%